"Medcomp-health care device" / Ahmad Shafiee Harfin ... [et al.] - Harfin, Ahmad Shafiee; Zainal Abidin, Muhammad Anuar; Raja Mohsin, Raja Mohamad Syahmir; Wan Azhar, Wan Ahmad Firdaus; Darami, Khuzaifi Akili (2017)
The team is developing a MedComp, known as a simple medical kit to check the vital signs, blood pressure, body temperature, food calories and to remind patient to consume medicine. It consists of checking the vital signs, blood pressure, blood glucose, body temperature, food calories and to remind patients to consume medicine. Some of the elders are having trouble to take the medication regularly or on time. This product is suitable for all generation who are concern about their own health. As the number of diabetes, hypertension and fever patients increase for each year. Thus, the team decided to help the society especially the elders by invent a user friendly medical box.